Sociocultural Perspective Among the Kiput of Baram: a Study of Kuala Tutoh and Benawa Communities - Zulkiflee, Zulfadzlee; Chuchu, Ifwah Fauzani (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
The Kiput of northern Sarawak, a small yet culturally significant indigenous group of about 450 people, remains understudied. Living in two settlements, Kuala Tutoh (mainly Christian) and Kampung Benawa (mainly Muslim), they navigate ethnic identity maintenance amid assimilation pressures and internal religious diversity. Using community-based ethnography, which incorporates participant observation, semi-structured interviews, and archival materials, this study employs thematic analysis with member checking to ensure community-grounded interpretations. Findings show that Kiput identity is sustained through shared historical memory, linguistic distinctiveness, and material culture, while religious affiliation is the primary organising principle shaping settlement patterns, livelihoods, and ritual life. Despite religious divergence, ethnic identification remains cohesive through enduring kinship ties. Younger members express reduced engagement with traditional markers yet selectively sustain aspects of their heritage. Cultural continuity persists alongside adaptive strategies, although structural factors such as state schooling, market pressures, and limited economic opportunities constrain intergenerational transmission, especially of the Kiput language. The study recommends strengthening indigenous land rights, reforming language education, supporting community-led heritage initiatives, and ensuring participatory development planning. The Kiput case reflects broader challenges faced by minority indigenous groups in Borneo as national development transforms ancestral landscapes and subsistence systems.